Factors related to resistance and support of organizational change - Orth, Michael Stephen, author; Hautaluoma, Jacob, advisor; Bell, Paul, committee member; Chen, Peter, committee member; Cropanzano, Russell, committee member; McCarthy, Anne, committee member (Colorado State University. Libraries, 2002)
This field study integrates a number of theories to better understand the causes of resistance and support of organizational change. Subjects were 193 em ployees from a state agency who com pleted a survey related to two specific changes the organization was in the process of im plem enting: a new perform ance evaluation system and a new pay-for-performance system . Resistance and support were operationalized in terms of specific behaviors rather than only as attitudes. Behavioral items w ere revised from Herscovitch and M eyer (2001) to measure active resistance, passive resistance, active support, and passive support. Four factors were proposed to predict resistance and support: 1) Readiness for change was com posed of two subscales: perceptions that the change was needed, and perceptions that the change would be successful; 2) Organizational justice was com posed of two subscales: procedural justice and interactional justice; 3) Perceived benefits of change was com posed of three subscales: costs and benefits to the organization, costs and benefits to the work unit, and costs and benefits to the individual; and 4) Individual needs was com posed of two subscaies: the need for stability and the need for control. Com m itm ent to change was proposed to mediate the effects of the four predictors on resistance and support behavior.

Confirm atory factor analysis of the behavioral item s supported a factor structure with resistance and support as two distinct but correlated latent factors. A passive-active factor w as not supported. Structural equation models with all predictors combined showed that readiness for change was most predictive of com m itm ent to change, resistance and support. The effects of each predictor were supported in separate structural equation models. Comm itm ent to change fully or partially mediated m any o f the relationships between the predictors and behavior based on the decomposition o f effects. The results indicate that, while all of the predictors w ere significant, it may be especially important for organizations to ensure that em ployees understand the need for the change, and feel confident the change will be im plem ented successfully. The study also suggests that im proved behavioral and predictor m easures w ould benefit both practice and research related to organizational change.